Mediação da Informação: estudo das práticas na Colônia de Pescadores “Benjamin Constant” Z5 em Lucena-PB - Nascimento, Deíse Santos do (2017)
This is an ethnographic research of artisanal fisheries in the municipality of Lucena-Pb and aimed to analyze the practices of information of mediation developed by the Fishery Community "Benjamin Constant, Z-5" for artisanal fisheries, and aims specifically to map the activities of fishermen on the beach of Lucena; to characterize the socioeconomic profile of fishermen and managers from the fishery community; to observe in what is based the relationship established between fishery community and fishermen; to understand aspects present in oral narratives of managers and fishermen from fishery community that can constitute as barriers in the process of information of communication; to present guidelines for the construction of an information regime and an information policy which promotes conversation between the fishermen from fishery community, the local fishermen and other institutions operating in the fisheries sector. This paper has as theoretical reference the literature from the fields of Science of Information and Sociology, through the point of view of sociological theory of secret from George Simmel, specifically addressing the three aspects of this theory: the secret, silence and conflict, and based on information as a social phenomenon, with support in the social paradigm from Capurro, regime and policy of information and studies from mediation of information. From the methodological point of view, the approach is ethnographic and qualitative, in which it was used the action research, the participant observation and the oral history to collect data, which were analyzed, emphasizing the significance of the facts and speeches as values the method of content analysis. The presentation of the analysis of the data was performed in two stages: initially the data collected through the registration effected with the fishermen and managers of the colony of fishermen and then performed the analysis made from the oral history narratives, with the lines and graphical representation, for best viewing set up relations and aspects of sociability. The final considerations present our impressions about the research field and the investigated object, and displays directions for future managers to make a more participative management, prioritizing the implementation of information practices that meets the needs of artisanal fisheries from the fishery community "Benjamin Constant", Z5.